Recent advances in PM6:Y6-based organic solar cells. (8th March 2021) - Guo, Qing; Guo, Qiang; Geng, Yanfang; Tang, Ailing; Zhang, Maojie; Du, Mengzhen; Sun, Xiangnan; Zhou, Erjun
Abstract : This review provides a detailed overview of PM6:Y6-based organic solar cells (OSCs), including the underlying mechanisms, terpolymers derived from PM6, ternary or quaternary OSCs, interfacial engineering and electrode progress. Abstract : The last two years have witnessed rapid progress in organic solar cells (OSCs), driven by the newly-developed nonfullerene acceptor (NFA) Y6, which contains an electron-deficient core-based central fused ring. Inspired by Y6, a lot of novel Y-series NFAs with A–DA′D–A structures and matched polymer donors have been synthesized. Besides developing donor/acceptor materials, there are also many other factors contributing to the advances in OSCs. This review focuses on the most classic PM6:Y6 material combination and summarizes the recent progress in OSCs. First, the underlying mechanisms for the such high performance of OSCs based on PM6:Y6 are introduced. Then, the modifications of the active layer are discussed comprehensively, which involves incorporating a third monomer into PM6 to synthesize a terpolymer, towards the construction of ternary and quaternary devices, and various processing technologies. Next, the development of an interfacial layer and electrode materials in PM6:Y6-based OSCs are also summarized and discussed. Finally, perspectives and directions for the further development of OSCs are proposed.